The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/gim.2016.66
|View full text |Cite
|
Sign up to set email alerts
|

Newborn genetic screening for hearing impairment: a population-based longitudinal study

Abstract: We delineated the longitudinal auditory features of the highly prevalent GJB2 p.V37I mutation on a general population basis and confirmed the utility of newborn genetic screening in identifying infants with late-onset or progressive hearing impairment undetectable by newborn hearing screening.Genet Med 19 1, 6-12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 40 publications
6
70
1
1
Order By: Relevance
“…Functional studies performed in cells and mouse models support this conclusion [4042]. In consistent with previous reports [6, 12–14], we observed that the HL phenotypes associated with p.V37I varied by onset type, disease site, and degree of HL, implying that other causes, especially environmental factors, influence p.V37I-mediated onset of HL. Notably, we also found that homozygous p.V37I might give rise to sudden deafness in children.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Functional studies performed in cells and mouse models support this conclusion [4042]. In consistent with previous reports [6, 12–14], we observed that the HL phenotypes associated with p.V37I varied by onset type, disease site, and degree of HL, implying that other causes, especially environmental factors, influence p.V37I-mediated onset of HL. Notably, we also found that homozygous p.V37I might give rise to sudden deafness in children.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the p.V37I (c.109G>A) variant of GJB2 has a high allele frequency (up to 10%) among East Asian populations [46]. This variant, harboring a missense substitution from valine to isoleucine at codon 37, was first identified by Kelley et al in 1998 [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 1993, when the first hearing loss gene was identified, more than 100 loci for deafness genes have been mapped and about 80 genes have been reported to be associated with non‐syndromic hearing loss ( Hereditary Hearing Loss Homepage ). Exhilaratingly, combining the GWAS analysis and the next‐generation sequencing technique, more than 150 loci have been discovered to date, including 54 autosomal dominant loci, 71 autosomal recessive loci, 5 X‐linked loci, two modifiers, and 1 Y‐linked locus (Wu et al, ). Although many new genes have been found, the most common genes associated with hearing impairment still are GJB2, SLC26A4, and mtDNA 12S rRNA .…”
Section: Introductionmentioning
confidence: 99%